Enantioselective modular synthesis of cyclohexenones: total syntheses of (+)-crypto- and (+)-cnfectocaryone - Franck, Géraldine Julie Anne-Marie; Brödner, Kerstin; Helmchen, Günter (Organic letters, 2010)
A modular synthesis of cyclohexenones is described and applied to the first enantioselective total syntheses of (+)-crypto- and (+)-infectocaryone. Key steps in the synthesis of cyclohexenones are an iridium-catalyzed allylic alkylation, nucleophilic allylation, and ring-closing metathesis. On the way to (+)-cryptocaryone, a catch and release strategy involving an iodolactonization/elimination and a regioselective C-acylation were used.